Effects of Mulching Materials on Growth and Yield of Brinjal - Subedi, Sandesh; Adhikari, Saroj (Agriculture Development Journal, 2024)
Brinjal; a valuable vegetable, is susceptible to weeds and moisture stress that can hinder growth and yield. Mulching might be a good option to control weeds and moisture to enhance growth and yield. So, an experiment was conducted with five treatments viz. black silver coated mulch (BSCM; 100 gauge), black polythene mulch (BPM; 300 gauge), straw mulch (8 t ha-1), corrugated fiber box mulch (CFBM), and an unmulch group replicated for four times in randomized complete block design at Horticulture Research Station, Pokhara in 2022. Results revealed that BSCM showed the highest marketable yield (23.78 t ha-1) which was statistically similar to straw mulch (20.44 t ha-1) and BPM (19.64 t ha-1) and the lowest (12.1 t ha-1) was observed in the unmulch (12.1 t ha-1). Plant height (134.1 cm), primary root length (40.95 cm), and secondary root numbers (23.25) were observed significantly higher in BPM which was statistically similar (p>0.05) with BSCM and straw mulch. The number of branches (7.325), the fruit length (23.2 cm), and fruit diameter (2.5 cm) were found higher in BSCM. Findings suggested that applying different types of mulching materials can effectively enhance the growth and yield of brinjal.